Prevalence of Flourishing in Argentine Adolescents - Rizzo, Ignacio Andrés (2022)
The aim of this study is to describe the levels of mental health from the dual factor model in a sample of Argentine adolescents in psychological treatment and in a sample of students. The samples included 552 young people between 12 and 18 years old. The SCL-90-R and the MHC-SF questionnaires were used. The flourishing levels were 31.6% in the sample under psychological treatment and 29% in the student sample. Most of adolescents in both samples fell into the moderate mental health category (treatment 57.9% vs student 59.5%). Between both samples, no significant differences were found in levels of mental health. The flourishing levels were low compared to other countries.